Building SimCity: How to Put the World in a Machine by Chaim Gingold (review). - Whelan-Shamy, Daniel (Technology & Culture, 2025)
"Building SimCity: How to Put the World in a Machine" by Chaim Gingold explores the history of the popular videogame SimCity and its influences, delving into the development of simulation technologies. The book highlights how simulation is not just confined to machines but is a social and culturally significant phenomenon. It contributes to software and game studies, shedding light on the interconnected worlds of education, urban planning, design, computation, business, and politics that SimCity bridges.